Kreowanie zachowań prozdrowotnych i antyzdrowotnych w kontekście stylu życia jako determinantu zdrowia - Janiszewska, Kamila; Polak, Jolanta; Rudnicka, Bogusława (Kultura-Społeczeństwo-Edukacja, 2024)
Among the factors determining health, the most important is lifestyle. An adult can influence what his or her life will be like by developing health habits acquired in childhood or by changing them over the course of gaining experience. The lifestyle developed by humans is associated with the creation of both positive and negative health behaviors. The most important healthy behaviors are not using stimulants, including drugs and alcohol, eating healthy, being physically active, taking care of your mental state, avoiding stress and finding ways to deal with it. The development of health behaviors is influenced by many factors, including: family, peer environment, personality, media. To keep your health in the best possible condition, you should lead a healthy lifestyle and change bad habits.